Elevating Reading Comprehension: Tailored Techniques for Non-English Majors - Zakaria, Dadang; Khoirunnisa, Maula (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2024)
Reading comprehension is essential for language acquisition and academic success, as it allows students to access information across all subjects. While numerous studies have examined the impact of various reading techniques on student comprehension, the process by which lecturers select and implement these techniques remains underexplored. This study addresses this gap by investigating the decision-making processes of lecturers when choosing techniques for teaching reading comprehension, particularly in non-English departments. Utilizing qualitative methods, including online surveys, semi-structured interviews, and observations, data were collected from lecturers at the Language Center of Universitas Muhammadiyah Malang. The findings reveal a two-stage selection process, with student English proficiency as the primary consideration, followed by their academic majors. Additional factors influencing technique selection include age, behavior, attitude, classroom environment, and course content. These insights are valuable for curriculum developers, lecturers, and researchers aiming to enhance language teaching practices and curricular development, ultimately leading to improved student outcomes and pedagogical advancement.